Hopefully a Good Life: Cosmopolitan Chinese Migrant Families in Urban Italy - Deng, Grazia Ting (Anthropologica, 2024)
Chinese residents have grown to be one of the most prosperous migrant groups in Italy since their mass migration from China in the 1980s. Alongside their rapid upward economic mobility, parents and children within the same families have shown generational differences in their understandings of the good life. While older generations believed that the good life means economic mobility, which is achieved through their labour and migration, younger generations’ definition of the good life, rooted in their negative experiences of racialization, is associated with social recognition. Such generational differences stem from the shifting tensions between the contested racial and national orders in association with Italy’s economic stagnation and China’s global ascendancy. Yet, both generations of these desiring subjects have manifested their own conceptions of cosmopolitan Chinese-ness to survive precarity and to aspire to a better life both economically and socially. Their family stories thus contribute to anthropological debates on how people envision their futures between hope and precarity, expectation and uncertainty, and privilege and disadvantages amid racialized class terrains, generational tensions, and geopolitical transformation of the world order.